The Effectiveness of CSR (Collaborative Strategic Reading) Strategy toward VIII Grade Students’ Ability in Reading at SMP N 11 Padang - Putri Melco; Jufri Jufri; Ratmanida Ratmanida (Universitas Negeri Padang, 2016)
This research aimed to figure out whether CSR gives positive effect toward VIII Grade students’ ability in reading at SMP N 11 Padang. Since this reserach was experimental research, the sample of this research were VIII B as the control group and VIII C as the experimental group selected by using cluster sampling. The data of this research was reading test (posttest) scores which were analyzed by using t-test. It was found that there was significant difference on student’ reading comprehension of grade VIII students who were taught by using Collaborative Strategic Reading (CSR) and the students taught by using conventional technique. The result showed that tcount was 6.7 and ttable was 2.00 in the level of significant 0.05 which means tcount was higher than ttable. Therefore, the null htpothesis (H0) was rejected and research hyphothesis (H1) was accepted. Finally, it could be concluded that CSR (Collaborative Strategic Reading) gives possitive effect toward students’ ability in reading.